1992
DOI: 10.1007/bf01741143
|View full text |Cite
|
Sign up to set email alerts
|

Significant antitumor effect of a synthetic lipid A analogue, DT-5461, on murine syngeneic tumor models

Abstract: The antitumor effect of a synthetic lipid A analogue, DT-5461, was investigated using syngeneic tumor models in mice. Intravenous injection of DT-5461 into mice transplanted with solid tumors of MethA fibrosarcoma, MH134 hepatoma, MM46 mammary carcinoma, Lewis lung carcinoma (3LL), and colon adenocarcinomas 26 and 38 resulted in significant reductions in the weight of all tumors except Colon 26, with marked hemorrhagic necrosis of tumor tissues. Efficacy was almost equal to that of an Escherichia coli-type syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Although TNF-a is involved in the antitumoral effect of lipid A, other factors are clearly involved. Thus while DT-5461 reduced the size of several murine tumors via a necrotic process and TNF-a secretion, (11,13,17) anti-TNF-a antibodies did not prevent tumor regression. (15) Furthermore ONO-4007 injected i.v.…”
Section: Cytokinesmentioning
confidence: 90%
“…Although TNF-a is involved in the antitumoral effect of lipid A, other factors are clearly involved. Thus while DT-5461 reduced the size of several murine tumors via a necrotic process and TNF-a secretion, (11,13,17) anti-TNF-a antibodies did not prevent tumor regression. (15) Furthermore ONO-4007 injected i.v.…”
Section: Cytokinesmentioning
confidence: 90%
“…) as phosphonooxyethyl glycosides to replace the labile α‐glycosyl phosphate . It was anticipated that these lipid A analogs might have improved bioactivities, such as antitumor activity, owing to their enhanced chemical stability.…”
Section: Chemical Synthesis Of Lipid a And Its Derivativesmentioning
confidence: 99%
“…According to the literature, E. coli lipid A and its derivatives had antitumor activities, thus the cytotoxicity of natural lipid A 1 and its synthetic analogs 54 – 56 to methylcholanthrene‐induced murine fibrosarcoma (Meth A fibrosarcoma) was studied in vivo . Compounds were administered to the mice at a dose of 100 μg/mL through the tail veins three times (7, 12, and 17 days after tumor inoculation).…”
Section: Chemical Synthesis Of Lipid a And Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthetic diglucosamine-based analog of Escherichia coli lipid A, DT-5461, possesses properties, such as lethal toxicity and pyrogenicity, that are considerably less endotoxic than those of LPS or synthetic lipid A and expresses effects against various murine syngeneic solid tumors (18,19). We previously demonstrated that DT-5461 significantly inhibited liver metastasis of L5178Y-ML25 lymphoma cells and lung metastasis of B16-BL6 melanoma cells during experimental metastasis and spontaneous metastasis in mice (31).…”
mentioning
confidence: 99%